PENGARUH SISTEM PEMBELAJARAN DAN KEPUASAN KERJA DOSEN TERHADAP KINERJA DOSEN DI STIKES KARSA HUSADA GARUT - Suliyawati, Eti (Universitas Pendidikan Indonesia, 2017)
Central issue in this study is teacher performance is not optimal, the researchers observed due to learning andjob satisfaction of teachers who have not been going well. On the basis of thought and consideration, theresearchers wanted to investigate further in the form of research thesis entitled